Face Lift Practice Patterns: An American Society of Plastic Surgeons Member Survey, 2000 and 2020. How Much Have We Changed?. Issue 6 (5th April 2022) - Sinclair, Nicholas R.; Kochuba, Andrew; Coombs, Demetrius M.; Couto, Rafael A.; Charafeddine, Ali H.; Grow, Jacob; Matarasso, Alan; Zins, James E.
Abstract : Background: In 2000, Matarasso et al. performed a survey of American Society of Plastic Surgeons members' face lift practice patterns. Since that publication, the aesthetic marketplace has changed dramatically, as have ancillary face lift techniques. In an attempt to detail these changes, we repeated that original survey, adding questions to address more recent technical issues and advances. The goal of this report was to define current face lift practice patterns, compare current patterns to the previous ones, and define recent advances. Methods: A 38-question survey assessing face lift techniques, perioperative management, complications, and concomitant procedures was electronically distributed to a random cohort of American Society of Plastic Surgeons members. Data were recorded and statistically analyzed utilizing the Pearson chi-square test. Results: A total of 251 forms were returned and analyzed. Details of demographics, face lift techniques, ancillary procedures, perioperative care, and complications are presented. Current results were compared to the previously published society member practice patterns delineated in the 2000 Plastic and Reconstructive Surgery publication. Conclusions: The basic approach of American Society of Plastic Surgeons members to the face lift operation has not changed dramatically over the past 20 years. The development of operative adjuncts, however, has been positive, including fat grafting techniques, concomitant use of skin resurfacing, and means of minimizing blood loss with tranexamic acid. In certain instances, respondents do not follow evidence-based guidelines for perioperative care. Finally, common complications of practicing members appear to coincide with published retrospective reviews.